The Influence of Leadership Style and Work Motivation on Employee Job Satisfaction at PT. Kendali Bumi Semesta - Pratiwi, Gading Putri; Hasanah (International Journal of Science and Society, 2024)
The purpose of this research is to identify and analyze the influence of leadership style and work motivation on employee job satisfaction at PT. Kendali Bumi Semesta. The population used in this study consisted of 40 employees, with a non-probability sampling technique, specifically saturated sampling, being applied to select 40 respondents as the sample. Data were processed using SPSS 25. The results of the study show that leadership style has a positive and significant effect, while work motivation does not significantly influence employee job satisfaction. The implications of these findings provide valuable insights for the company in developing human resource management strategies, focusing on enhancing positive leadership styles. Furthermore, work motivation can be evaluated by emphasizing better encouragement and enthusiasm to ensure optimal employee job satisfaction.